Addressing the Humans in the Delivery Room—Optimising Neonatal Monitoring and Decision-Making in Transition - Christoph E. Schwarz; Bernhard Schwaberger; Alice Iride Flore; Robert Joyce; Simon Woodworth; Frederic Adam; Eugene M. Dempsey (Children)
During the first minutes of life, complex dynamic processes occur, facilitating a normal transition to ex utero life. In healthy term infants, these processes typically occur with minimal intervention required but are often more challenging for the preterm infant. These challenges involve not only the physiological processes encountered but also an organizational process: that of a team of healthcare providers led by a neonatologist, establishing a diagnosis based on clinical and technical information and initiating time-critical and potentially life-altering interventions. In this narrative review, we highlight the challenges of both processes. We explore the role and limitations of well-established and newer potential monitoring modalities, in particular respiratory function monitoring and cerebral near-infrared spectroscopy, to optimally inform the team in regards to physiological processes. We also evaluate the important role that human factors play in the process of decision-making. Both are important for optimal performance to enable successful transition and thereby reduce short- and long-term problems. We identify research goals to inform future studies to further optimize technological and human aspects in the first minutes of life.